Síntese de geopolímeros à base de metacaulim e lama de rejeito de minério da barragem do Córrego do Feijão (Brumadinho - MG) - Jouber Paulo Ferreira (2021)
The gross production of iron ore in Brazil has generated high volumes of tailings, commonly disposed of in upstream dams. This disposal method has recently caused accidents, considered severe or very severe. Furthermore, the construction sector has caused environmental impacts with regard to the use of mineral resources and CO2 emissions. To this effect, research has been conducted in the search for alternative binders that incorporate dam tailings. One of the binders capable of replacing Portland cement, in some situations, is geopolymer cement. The geopolymeric paste, geopolymer, is produced by alkaline activation of amorphous aluminosilicates, commonly using activators in solution (two part). Some of the studies use iron ore tailings as the precursor, but few studies that incorporate these tailings use the one part method. This research evaluates the synthesis of geopolymers using iron ore tailings slurry (IOT) as a mass substitution for 12.5%, 22.5% and 50.0% of metakaolin, and NaOH and Na2SiO3 as solid activators. Immediately after the synthesis of the slurries, isothermal calorimetry was performed. After 28 days of curing at room temperature, the occurrence of alkaline activation was evaluated by X-ray diffraction, by Fourier transform infrared spectroscopy, calorimetry, and physical-mechanical tests. The results indicated that the addition of IOT reduced the heat of reaction released in the synthesis of the geopolymer, as well as the occurrence of alkaline activation for all formulations analyzed. However, it was observed that the use of IOT acts to increase the porosity and the water absorption in the synthesized samples, besides reducing the compressive strength at ages 21 and 28 days. Such results indicate that the IOT did not act as a filler, acting as a dilutant of the metakaolin and/or porous addition. However, at 3 and 7 days, the use of IOT did not influence the compressive strength of geopolymers, which could indicate that the proportion of the activator solution (water + solid activators) was adequate at these ages, jeopardizing the reaction at later ages.